Fundamentals of Entrepreneurship Ent300: Fresh Serunding Enterprise / Nurfatimah Ahmad Shah ... [et al.] - Ahmad Shah, Nurfatimah; Pirit, Evelyn; Alisiew, Emyeziana; Rambely, Khairul Anwar (2011)
The name of our company is FRESH SERUNDING ENTERPRISE. The form of business that we operate is partnership, which consists of four members. Each member contributes certain amount of capital as agreed in agreement later before these businesses have been established. The business activity that we run is produce and supply the floss known as serunding for those people who like to eat it and to satisfy the needs and wants of customer. Our business will be held in Satok, Kuching.